KEMAMPUAN MENYIMAK SISWA KELAS XI TET 1 SMK NEGERI 5 KUPANG DALAM MENGANALISIS TEKS BERITA AUDIOVISUAL - Minrayati Adu; Labu Djuli; Margareta P. E. Djokaho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The focus of this study is the listening comprehension skills of class XI TET 1 students at SMK Negeri 5 Kupang in analyzing audiovisual news texts. Listening comprehension is a fundamental foundation in language learning that frequently faces challenges related to student focus and retention. Therefore, this study aims to describe the listening skills of class XI TET 1 students at SMK Negeri 5 Kupang in analyzing audiovisual news texts. Audiovisual media was utilized to attract students' interest and provide a more concrete and contextual learning experience, as students not only hear information but also observe the context and expressions supporting the message's meaning. This research employed a descriptive qualitative method, underpinned by Information Processing Theory and Writing Theory. Based on the data analysis regarding the students' listening ability in analyzing audiovisual news texts, the results across the elements (5W+1H) aspect revealed that 2 students (9%) achieved the "very good" category, 13 students (59%) were in the "good" category, and 7 students (31%) fell into the "fairly good" category. In the news text structure aspect, 6 students (27%) reached the "very good" category, 10 students (45%) achieved "good", 4 students (18%) were categorized as "fairly good", and 2 students (9%) fell into the "poor" category. In terms of linguistic features, 9 students (40%) scored "very good", 11 students (50%) scored "good", 1 student (4%) scored "fairly good", and 1 student (4%) scored "poor". Overall, out of the 22 students studied, 4 students (18.18%) were categorized as very good, 4 students (18.18%) as good, 7 students (31.81%) as fairly good, and 7 students (31.81%) as poor in listening to and analyzing audiovisual news texts. Collectively, these findings indicate that the listening skills of class XI TET 1 students at SMK Negeri 5 Kupang in analyzing audiovisual news texts are generally categorized as good and have successfully surpassed the Minimum Mastery Criteria (KKM) set at 75. The implementation of audiovisual media proved highly effective in assisting students to enhance deep comprehension and strengthen memory retention when examining news text components. Based on these conclusions, the researcher presents several strategic recommendations for instructional practice. Indonesian language teachers are expected to optimize and integrate varied audiovisual learning media based on current issues relevant to students' lives. Furthermore, teachers are advised to provide targeted exercises to reinforce critical reasoning, particularly in analyzing structural components and linguistic features with higher complexity. Thus, the quality of listening instruction can be continuously and equitably improved for all students.